(untitled) (Olhar de Professor, 2021)
The Covid-19 pandemic caused unexpected reflexes in the most diverse fields, including education. In a short period, teachers used to the day-to-day classroom experience had to adapt their routine to online classes. Considering this context, based on bibliographic research and case study this study aims to describe how our adaptation to online classes in Higher Education in Law took place, analyzing what were the main challenges and the strategies used to face them. We initially noticed a transition phase, marked by the lack of knowledge about technologies, adaptation to new protocols and virtual dynamics. Subsequently, it was possible to identify long-term challenges, such as poor student participation, difficulty with the peculiarities of virtual time and adaptation to technological tools. Finally, it was possible to identify good practices for remote teaching, with emphasis on the use of active methodologies and the creation of moments of welcoming students.